High Pressure Sintering of Al2O3-CNT Nanocomposites - Kuskonmaz, Nilgun; Ozturk, Zeynep Taslicukur (CARL HANSER VERLAG, 2014)
In this study, Al2O3-CNT nanocomposites were sintered at 800-1000 degrees C under 5 GPa for 10 minutes using two different powders as starting material, gamma-Al2O3 and AlOOH, respectively. The effect of transition alumina powders on the properties of the high pressure sintered Al2O3-CNT nanocomposites were studied. Al2O3 ceramics have been widely used for structural, electrical, and optical applications. Carbon nanotubes (CNTs) have recently been considered as reinforcing elements in ceramic matrix composites due to their unique mechanical properties. Reactive pressure sintering at low temperatures took place during the fabrication of CNT reinforced ceramic composites to avoid the agglomeration of carbon nanotubes. The hardness and densities were investigated and correlated with the microstructure of the dense materials. SEM analysis was used to determine the CNT distribution in the matrix, the morphology, and size of the particles.
Keywords: Materials testing; ceramic matrix composite (CMC); microstructures; carbon nanotube (CNT); alumina; CARBON; POWDERS; PHASE; Materials Science